2016
DOI: 10.5993/ajhb.40.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Texting to Increase Adolescent Physical Activity: Feasibility Assessment

Abstract: Objective Feasibility trials assess whether a behavior change program warrants a definite trial evaluation. This paper reports the feasibility of an intervention consisting of Self Determination Theory-informed text messages, pedometers, and goal prompts to increase adolescent physical activity. Methods A four-group randomized design with baseline and immediate post-study assessments was used. Groups (pedometer; pedometer + goal prompt; pedometer + goal prompt + theory-informed texts; no-treatment control) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 84 publications
5
46
0
1
Order By: Relevance
“…Long‐term interventions that ensure continuous engagement of users are required for the actual achievement of improved physical fitness with BMI and body weight outcomes. Personalized motivational messages are effective in targeting the modification of lifestyle variables (Thompson et al, ) based on the present meta‐analysis. Furthermore, caution should be taken regarding the information provided via a mobile phone.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Long‐term interventions that ensure continuous engagement of users are required for the actual achievement of improved physical fitness with BMI and body weight outcomes. Personalized motivational messages are effective in targeting the modification of lifestyle variables (Thompson et al, ) based on the present meta‐analysis. Furthermore, caution should be taken regarding the information provided via a mobile phone.…”
Section: Discussionmentioning
confidence: 85%
“…Six studies (Chen et al, ; Direito, Jiang, Whittaker, & Maddison, ; Lubans et al, ; Smith et al, ; Thompson et al, ) examined the effects of mobile phone intervention on physical activity; however, one study used a self‐reported questionnaire that differed from the evaluation method used in other studies where the actual activity time and movements were counted and thus, it was excluded in the meta‐analysis (Figure ). One study by Direito et al () evaluated two different health applications; thus, data were pooled from six interventions for meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obdobně jako Bürgi a de Bruin (2016), i výsledky naší studie poukazují na vhodnost zacílit intervenční programy zvyšující PA žáků do období mimoškolních dní. Přitom je však třeba brát v potaz sedavé chování, které často nahrazuje PA (Carlson et al, 2016), případně intervence doplnit o účinnou motivaci (Thompson et al, 2016). Z předložených výsledků vyplývá, že žáci mají zkreslenou představu o úrovni sobotní PA svých spolužáků.…”
unclassified